THE PESANTREN EDUCATIONAL MANAGEMENT AND BUILDING RELIGIOUS ISLAMIC GENERATION - Mawardi Lubis (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2015)
The objective  of this research was to understand the pesantren educational management and building religious  Islamic  generation. The  approach be  used  in research was  qualitative  participant and  descriptive analysis method. The data were  collected through live explanation by the Bengkulu Islamic Students Pesantren (Ma’had  ath-Thullab  al-Islami)  Dr. H. Mawardi  Lubis, M.Pd manager as  a unit  analysis  of the  research. The research result indicates that the pesantren have been implementing a traditional  and centralistic educational management ( all in kyai management). Than, the pesantren have  been gaving good contribution in building religious Islamic generation.